Atividade antigenotóxica dos extratos de Celtis iguanaea (Jacq.) Sargent e Lafoensia pacari A. St.-Hil. em células somáticas de Drosophila melanogaster - Pereira, Karla de Castro (2010)
The possibility of natural substances, derived from medicinal plants, modulate the cellular response to the mutagenic agents activity has emerged as an important mechanism in the discovery of new effective natural treatments. The aim of this work was evaluate the possible toxic, genotoxic, and antigenotoxic effects of two Brazilian Cerrado plants, which are used in folk medicine. Celtis iguanaea Jacq. Sargent (Cannabaceae), known in the state of Goiás (Brazil) as “esporão-de-galo”, has been used to treat rheumatism, asthma, body pain, colic, poor digestion, urinary infections and kidney disfunctions. Lafoensia pacari A. St.-Hil. (Lythraceae) is known popularly as “pacari” or “mangaba-brava” and has been used in traditional medicine to treat gastric ulcers, inflammation, and scar healing. The present study used the Somatic Mutation and Recombination Test (SMART), which evaluates, simultaneously, in vivo recombinational and mutational events. Third-stage larvae derived from the standard cross were used in the extract treatments. Initially, the toxicity of different concentrations of aqueous extract of leaves of Celtis iguanaea (EaqLC) and ethanol extract of leaves of Lafoensia pacari (EELL) was evaluated. The EaqLC showed no toxicity, because there was no difference between the number of surviving flies in the extract series and control treatments. Flies treated with the EELL test concentrations showed a survival rate above 40%. For genotoxic evaluation, the larvae were treated with different concentrations of EaqLC and EELL and distilled water (negative control). Both extracts did not significantly increase the frequencies of spots with mutant hair compared to negative control, so no genotoxic activity was detected. In antigenotoxic evaluation, the larvae were co-treated with different concentrations of EaqLC and EELL associated with mitomycin C (MMC), and MMC alone (positive control). The antigenotoxic analysis of trans-heterozygous individuals treated with EaqLC + MMC and EEL+MMC showed a reduction in the frequency of mutation and/or mitotic recombination due to inactivation or blockage action of these extracts on the action of MMC. The comparison of the analysis of trans-heterozygous (MH) and TM3 heterozygous (BH) descendents allowed quantifying separately the contribution of the inhibition of mutation and recombination in the total antigenotoxicity induced by the two extracts studied. This was possible because the products of recombination in BH individuals are unviable. The results showed that the proportion of mutagenic and recombinagenic events induced by EaqLC+MMC or EELL+MMC was not significantly different from MMC treatment. In summary, the overall results indicated that the EaqLC and EELL extracts do not exhibit any toxic or genotoxic effects, but were able to block or inactivate the genotoxicity of MMC, acting as desmutagenic agents.